2018
DOI: 10.1093/bioinformatics/bty215
|View full text |Cite
|
Sign up to set email alerts
|

Ribopeaks: a web tool for bacterial classification through m/z data from ribosomal proteins

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The mass of ribosomal subunits can be directly calculated from genomic sequences, as they are relatively conserved and rarely post-translationally modified. Their potential to serve as MALDI-TOF MS biomarkers has been applied to clinically relevant phylogenetic groups ( Hotta et al., 2010 ; Ziegler et al., 2015 ; Rothen et al., 2019 ), and multiple databases using marker masses predicted from genomic data are now available ( Kassim et al., 2017 ; Ojima-Kato et al., 2017 ; Tomachewski et al., 2018 ). A ribosomal marker based approach has successfully been applied to distinguish between subspecies and clonal complexes within species such as Streptococcus agalactiae and Escherichia coli ( Matsumura et al., 2014 ; Lafolie et al., 2015 ; Rothen et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mass of ribosomal subunits can be directly calculated from genomic sequences, as they are relatively conserved and rarely post-translationally modified. Their potential to serve as MALDI-TOF MS biomarkers has been applied to clinically relevant phylogenetic groups ( Hotta et al., 2010 ; Ziegler et al., 2015 ; Rothen et al., 2019 ), and multiple databases using marker masses predicted from genomic data are now available ( Kassim et al., 2017 ; Ojima-Kato et al., 2017 ; Tomachewski et al., 2018 ). A ribosomal marker based approach has successfully been applied to distinguish between subspecies and clonal complexes within species such as Streptococcus agalactiae and Escherichia coli ( Matsumura et al., 2014 ; Lafolie et al., 2015 ; Rothen et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the authors reported an outperformance of the model compared to existing benchmarks. Furthermore, Tomachewski et al [97] presented a bacterial classifier tool based on r-protein data. The application compares m/z data from MALDI-TOF MS analysis with ML models stored in a database that contains more than 28,500 bacterial taxonomic records.…”
Section: Detection and Identification Of Microorganismsmentioning
confidence: 99%
“…An example is the lately introduced wide-ranging bacterium classifier tool, called Ribopeaks; it was created using r-protein data from the Genbank and now consists of~30,000 bacterial taxonomic records. The principle of its use is that it compares the incoming m/z data from the analysis using its own models in order to taxonomically classify the bacteria [18].…”
Section: Future Trends Of Msmentioning
confidence: 99%